A novel differentiated retransmission scheme for MPEG video streaming over wireless links. (23rd February 2007) - Hou, Fen; Ho, Pin-Han; Shen, Xuemin (Sherman)
With the dramatic improvement on scalability and flexibility of the MPEG-4 standard, video-based services are expected to become one of the most important bandwidth consumers in the next-generation wireless networks. However, providing a quality video delivery over wireless networks poses many challenges due to a high Bit Error Rate (BER), time-varying characteristics of wireless channels and a stringent delay and delay jitter requirement for real-time applications. To solve these problems, a suite of interoperable approaches must be devised for enhancing the robustness of video streaming to the error-prone environment. In this paper, we propose a Differentiated Automatic Repeat Request (DARQ) scheme for MPEG video streaming over wireless links, in which the inter-frame dependency and error propagation are jointly considered and a specific retransmission attempt is assigned to each frame in a Group of Pictures (GOP) according to its significance in the reconstruction of the video at the end-user. Both analytical modelling and extensive simulations have been conducted to verify the proposed scheme. The results demonstrate that the playable frame rate can be substantially improved by using the DARQ scheme compared with that by ARQ schemes employing the uniform retransmission persistency for all frames or assigning the retransmission persistency only depending on the frame type.